Analysis of the Output Power 10Wp Polycrystalline Photovoltaic Panels on the Effect of Sand Dust and Brick Dust - Ike Bayusari; Hermawati; Caroline; Rahmawati; Anderssen Hutama (Jurusan Teknik Elektro Fakultas Teknik Universitas Sriwijaya, 2024)
Polycrystalline Photovoltaic Panels are a device that plays a role in converting photon energy from sunlight into electrical energy. Installing photovoltaic panels outdoors can result in dust buildup on their surfaces, potentially affecting the panel's output power because the light that can be converted into electrical energy is limited due to being covered by dust. An experiment was carried out by sprinkling 3 grams of sand and brick dust measuring less than 425 µm on the panel. Based on measurements and analysis, panels without treatment show the highest voltage, current and output power values of 12.69 V, 0.28 A and 3.55 W respectively. Meanwhile for panels with sand dust, the voltage values are 12, 19 V, current 0.244 A, and output power 2.97 W. Panels with brick dust recorded the lowest voltage values of 11.84 V, current 0.211 A, and output power 2.49 W. There was a decrease in the values of voltage, current, and output power on panels without treatment compared to panels exposed to dust. Panels with sand dust produce higher output power compared to panels exposed to brick dust, due to the different characteristics of sand dust which is coarser with larger particles compared to brick dust which has a finer texture and smaller particles. As a result, the larger sand dust particles cause less panel surface area covered by dust compared to brick dust, so that more sunlight can be converted into electrical energy.